Inmigration and Education: an open story beyond academics - Esteban Frades, Santiago (Avances en Supervisión Educativa, 2016)
Migrations are still a global problem unresolved; nowadays, there are more movements of migrants than at any other time in human history. People escape from poverty, war and poor living conditions. We are unable to address the phenomenon of immigration without understanding that it is caused by inequalities and poverty. It affects people because it causes: family breakdown, dislocation, changes of social class and role and difficulty in integration.Vague answers are given to the problem as the current situation of refugees happens. Racism and xenophobia are increasing as we can see on the elections in different European countries. They must remove the political models of rejection and instead adopt different models based on tolerance.A single educational vision would be reductionist; it is necessary to review other perspectives that affect immigration in Spain: sociological, labor, political and legal. When immigrants arrive several issues need to be addressed, not only for education but the legality, language, housing, work, health, cultural and religious exercise, social participation, etc.Their right to education is well covered by legislation. There are enough studies and investigations that relate the most relevant regarding the situation of immigrant students and the qualitative conditions of schooling in general are positive. Finally, three situations for which it is necessary to take action are described: the unfavorable situation in secondary education, the danger of exceeding the limit of 30% of this pupils in schools as pointed out by the Ombudsman and instability or insecurity schooling immigrant students for certain labor mobility of their families.
Keywords: immigration; migration; rights; education; immigrant students